COVID-19 pandemic and its psychological impact among healthy Portuguese and Spanish nursing students - Carlos Laranjeira; Ana Querido; Goreti Marques; Mafalda Silva; Daniela Simões; Luísa Gonçalves; Rita Figueiredo (Health Psychology Research)
Few studies have explored the impacts of COVID-19 and lockdown on the mental health of undergraduate nursing students. This study aimed: a) to explore perceived stress among undergraduate nursing students in Portugal and Spain during the COVID-19 pandemic outbreak; and b) to analyze several COVID-19 related factors and psychological issues that may be associated with perceived stress. A cross-sectional study was conducted with a convenience sample of Portuguese and Spanish undergraduate nursing students (n=1075). The data gathered included demographic information, questions about COVID-19 related factors, and psychological issues. Data were analyzed using multiple logistic regression with a degree of significance at p<0.05. High perceived stress scores were found in 558 participants (51.9%). Students with high perceived stress most likely had a COVID-19 diagnosis in their household; their household income had been affected by the COVID-19 pandemic; experienced difficulty falling asleep or sleeping all night; consumed junk food in excess; neglected their appearance; felt headaches, stomach aches, and back pain; and lacked the patience or desire to exercise. Additionally, high perceived stress was negatively associated with life satisfaction. The results provide evidence that infectious diseases, such as COVID-19, may significantly influence mental health. Further research should explore the long-term psychological effects of the COVID-19 pandemic among nursing students.